Cause-related marketing and service innovation in emerging country healthcare: Role of service flexibility and service climate - Kumar, Pradeep; Singh, Sanjay Kumar; Pereira, Vijay; Leonidou, Erasmia (My University, 2020)
Purpose: The purpose of this paper is to identify the constituents of cause-related marketing (CRM) capabilities in the context of an emerging market healthcare sector, by incorporating the resource-based view alongside the dynamic capability perspective. Moreover, the authors aim to illustrate how the typologies of CRM capabilities help to achieve service innovation whilst taking into consideration the role of service flexibility (SF) and service climate. Design/methodology/approach: The authors develop a research framework through a representative and novel case study in the Indian healthcare market by utilizing and analyzing the subject-specific literature. Furthermore, a quantitative survey of healthcare professionals was conducted to assess the relationships utilizing PLS–SEM. Findings: After identifying the constituents of CRM capabilities, the study confirms the mediating mechanism of SF between CRM capabilities and service innovation. Furthermore, findings from the study suggest that service climate positively moderates the relationship between CRM capability and SF. Research limitations/implications: The study was conducted in the emerging country healthcare market of India. Thus, the generalizability of the framework needs to be tested in a similar or contrasting context. Furthermore, the sample size for the study was limited to healthcare professionals, and the customer’s perspective was missing. Originality/value: This paper is a first step to identify the specific dimensions of CRM capability and explain it as a higher-order factor. The study further provides an integrative framework that includes CRM capability, service innovation, SF and service climate. More specifically, it enhances the understanding of the constituents of the CRM capabilities and their influence on service innovation.
Keywords: Cause-related marketing (CRM) capability; Emerging markets; Service climate; Service flexibility; Service innovation